2011
DOI: 10.1213/ane.0b013e3182222a66
|View full text |Cite
|
Sign up to set email alerts
|

Learning Endotracheal Intubation Using a Novel Videolaryngoscope Improves Intubation Skills of Medical Students

Abstract: Education using a video system mounted into a traditional Macintosh blade improves intubation skills in medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 18 publications
3
41
1
1
Order By: Relevance
“…Most previously published studies on C-MAC have been conducted using experienced personnel [8][9][10], whereas at least one has used medical students [17]. We decided to involve our residents in this study to simulate actual in-training conditions, reduce variability in laryngoscopy performance, and reduce training time.…”
Section: Discussionmentioning
confidence: 99%
“…Most previously published studies on C-MAC have been conducted using experienced personnel [8][9][10], whereas at least one has used medical students [17]. We decided to involve our residents in this study to simulate actual in-training conditions, reduce variability in laryngoscopy performance, and reduce training time.…”
Section: Discussionmentioning
confidence: 99%
“…Video can also facilitate assessment with global rating scores [65]. A number of studies describe the benefit of imaging the larynx with videolaryngoscopes to assist instruction during training in laryngoscopy [66][67][68][69].…”
Section: ó 2011 the Authorsmentioning
confidence: 99%
“…Several studies have demonstrated that compared to the training with the DL, video-assisted instruction with a combined VL/DL device may shorten the learning curve of tracheal intubation for students, improve intubation success rate and decrease rate of oesophageal intubation (72)(73)(74)(75). Following training, moreover, the novices trained by using a combined VL/DL device perform better with respect to number of intubation attempts, needs of adjunct maneuvres and teeth trauma in simulated difficult airway conditions compared to those trained by using a Macintosh DL (76).…”
Section: Should Videolaryngoscopy Be Used For All Intubations?mentioning
confidence: 99%